"Parasitic Contamination of Vegetables from Farms and Markets in Tehran" - MJ Gharavi; MR Jahani; MB Rokni (Tehran University of Medical Sciences, 2002)
Because of endemic parasitological infectious diseases in Iran and contaminated vegetables, as one of the most important ways of contamination, carried out a parasitical study on 263 vegetable samples from 44 farms in the suburbs of Tehran city, and also 166 vegetables samples from 20 green grocery markets in the same city. From 263 samples of farms 147 cases (65%) of contamination were recorded, of which 43 cases (16/5%) of human pathogenic parasites were isolated. In this study various techniques were used such as: Baermann funnel, centrifuging of plants and soil, temporal precipitation procedure and so on. Ova and parasites such as Ascaris lumbricoides, Trichuris trichiura, Trichostrongylus sp. Toxocara sp. Larvae of Nematodes, protozoa cysts like Amoeba sp. Giardia lamblia and some flagellatae were seen. The highest percent of contamination was detected in leek and parsley and the lowest one was detected in tarragon. The results show that vegetables could be a potential source of parasitic infection.